PENINGKATAN KEMAMPUAN GURU DALAM PENYUSUNAN SOAL HIGHER ORDER THINKING SKILL (HOTS) MELALUI WORKSHOP: SDN SUMBERSARI 3 KECAMATAN MAESAN KABUPATEN BONDOWOSO (Mitra Pendidikan, 2020)
The low ability of teachers in the preparation of high-order thinking skills (HOTS) questions at SDN Sumbersari 3, Maesan sub-district is the focus of research. This is obtained from the results of a study of 5 questions of high-order thinking skills (HOTS) using an average of 54 multiple choice production techniques with unfavorable criteria and by using an average description assessment technique of 58 with unfavorable criteria, with an analysis of the material aspects. On average 60. The purpose of this study was to improve the ability of teachers in the preparation of high-order thinking skills (HOTS) questions at SDN Sumbersari 3, Maesan District, Bondowoso Regency, 2017/2018 academic year. The conclusion of the research using workshops shows an increase in the ability to compile higher order thinking skills (HOTS). This conclusion is supported by the results of a review of 5 questions of high-order thinking skills (HOTS) using multiple choice production techniques on average in cycle 1 of 75 with good criteria and cycle 2 of 87 with very good criteria. While the results of the review of 5 questions on higher order thinking skills (HOTS) using the average description in cycle 1 were 80 with good criteria and cycle 2 was 89 very good criteria. The results of the interview at the end of cycle 2 stated that after the principal's actions were taken, in the preparation of high-order thinking skills (HOTS) questions in schools it had been carried out independently according to class assignments, the average teacher was able to compile high-order thinking skills (HOTS) questions. well, the teacher is able to use multiple choice techniques, short entries, short answers and descriptions easily.